PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN ONLINE - Wayan Tunti Wiriani (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
Many things affect the quantity and quality of student learning which will ultimately affect their learning outcomes. The success rate of students both changes in knowledge, skills or attitudes can be seen from the learning outcomes. In the learning process, each student has various characteristics. There are students who can participate in teaching and learning activities well and there are also students who have difficulty in participating in learning activities. The purpose of this study was to determine the effect of independent learning on student learning outcomes in online learning and to determine student learning outcomes in online learning. This research is a quantitative research. The research method used is a survey method with correlational analysis, namely examining the relationship between independent variables and dependent variables. The variables studied were students' learning independence (X) and learning outcomes (Y). Based on the results of research and hypothesis testing, it can be concluded that the results of the study are as follows: There is a significant positive effect of learning independence on learning outcomes. It is proven by the simple correlation coefficient value which is positive, significant correlation test with Sig 0.05, and regression coefficient test with Sig 0.05; there is a significant positive effect of learning independence on learning outcomes. Each increase in learning independence units will significantly increase learning outcomes by 2,041 unitsKeywords: Independent Learning, Online Learning, Learning Outcomes